Analisis Standar Kerja Karyawan Bagian Produksi Guna Menunjang Produktivitas Kerja pada Konveksi Bandung Muara Bulian - Siti Marlina; Irwanda Amir (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT STIE-GRAHA KARYA MUARA BULIAN, 2022)
The purpose of this study are (1) To find out the Employee Work Standards of Production at the Bandung Convection at Muara Bulian (2) To find out Work Productivity at the Bandung Convection at Muara Bulian (3) To analyze the Employee Work Standards of the Production Section to Support the Productivity of Work at Convection Bandung in Muara Bulian. The research method used is descriptive qualitative with a quantitative approach. The analytical tool used is qualitative descriptive analysis, standard time analysis and productivity analysis. The results showed basically Bandung Convection did not have a standard work standard but the business owner always emphasized to employees to work well and on time so that the work results obtained had a maintained and appropriate quality and workmanship in accordance with the agreement made between the business owner and consumer. Based on the calculation of the time between the standard time determined by the leader and the time used, a conclusion can be drawn if the time used by employees to do their work is considered to be very productive, this is because the time spent is smaller than the standard time determined by the leader. With the number of orders 224 sheets of clothes and pants with a standard time determined by the company for 1 sheet of clothes or pants for 105 minutes with a total workforce of 8 people, and working hours in a day for 8 hours (480 minutes), the analysis can be concluded in this research is very productive, it is seen from the time available and the time spent.